MODEL PENDEKATAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH BERBASIS NILAI-NILAI BUDAYA, HUMANISTIK, DAN NASIONALISME DALAM PENGUATAN PENDIDIKAN KARAKTER - Yulius Rustan Effendi (LPPM Universitas Negeri Yogyakarta, 2020)
This study aims to describe the reasons for applying the cultural, humanistic, and nationalism approaches by school principals in supporting transformational leadership behavior. In addition, to explore the steps of the principal's transformational leadership role based on three forms of approach in the implementation of character education strengthening programs. This study used a qualitative approach, case study design. Data collection through in-depth interviews, participant observation, and learn documentation. Data analysis used a modified analytic analysis method. The level of credibility, transferability, dependability, and confirmability examines the validity of the data. The research findings explain that culture or tradition greatly influences the school environment, personal excellence, and encouragement to revive the humanistic spiritual inspirational figure, as well as the image of the school foundation managed by the Military unit, Kodam V-Brawijaya, being the basic reason that inspires the principal to use a cultural, humanistic approach, and nationalism. Besides that the steps of the principal's transformational leadership role based on cultural, humanistic, and nationalism approaches have an effective effect in optimizing the implementation of character education strengthening in schools.